Do Collaborative Governance Affect Village Community Empowerment And Village Development? - Muchlas, Mustari Kurniawati; Guohua, Wong (Cita konsultindo, 2023)
In 2017, most villages in Berau Regency, East Kalimantan, Indonesia, were still classified as disadvantaged villages, despite the village fund policy. It needs cooperation with other sectors to assist local governments in developing villages with limited resources and budgets. SIGAP is a collaborative program of the Berau Regional Government, Gadjah Mada University, Dharma Bhakti Berau Coal Foundation, and the Natural Resources Conservation Foundation in assisting villages in the Berau Regency. The purpose of this study is to see collaborative governance in improving village development through the SIGAP Program. This study used a quantitative survey method with a sample of 83 respondents of SIGAP fighters from 100 villages in Berau Regency. The data analysis used in this study is the Smar tPLS program version 3.3. The results showed that Collaborative Governance affected village community Village empowerment affected Village Development and Collaborative governance and community village empowerment affected Village development